Short and mid-term clinical and radiological results in ligament-cutting total knee arthroplasty (Annals of Medical Research, 2022)
Aim: In our study, it was aimed to present our retrospective clinical and radiological short and medium-term results in patients who underwent total knee prosthesis and compare them with the literature.Materials and Methods: 74 knees of 55 patients who were followed-up regularly from 114 patients who underwent primary ligament-cutting cementitious total knee prosthesis between January 2015 and 2020 in the Department of Orthopedics and Traumatology of our clinic were included in this study. Our study is a retrospective study, and our patients were evaluated clinically according to the American Knee Society scoring system before and after surgery, while they were evaluated radiologically according to the Total Knee Replacement Radiological Evaluation Criteria. Analyzes were performed with IBM SPSS 25.0 program and p
Keywords: Arthroplasty; ligament cutters; knee society score; infection